Systems Engineering and Industrial Engineering. Issue 1 (26th September 2022) - Parnell, Gregory S.; Kenley, C. Robert; Specking, Eric; Pohl, Edward
Abstract: Systems engineering overlaps with many fields, such as industrial engineering, engineering management, operations research, project management, and design engineering. In fact, the main industrial engineering body of knowledge, the Industrial and Systems Engineering Body of Knowledge, includes systems in the title and includes a section on systems design and engineering, which References the Systems Engineering Body of Knowledge. This paper describes the similarities and differences between systems engineering and industrial engineering based upon the respective standards, handbooks, and bodies of knowledge. Based on this assessment, we describe potential roles systems engineers and industrial engineers perform during a system's life cycle. We conclude with a summary of our paper.